2015
DOI: 10.1007/s40618-015-0363-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D during pregnancy: why observational studies suggest deficiency and interventional studies show no improvement in clinical outcomes? A narrative review

Abstract: A considerable number of studies have examined vitamin D status during pregnancy.Although data from observational studies denote vitamin D hypovitaminosis (deficiency or insufficiency) during pregnancy, data from interventional (supplementation) trials fail to reveal a significant impact on maternal and offspring health. The aim of this review was to critically appraise the methodology of the published trials in an attempt to explain the difference between observational and supplementation data. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 75 publications
0
24
0
1
Order By: Relevance
“…Accordingly, available data from RCTs on effects of vitamin D supplementation on birth weight do not clearly support findings from observational studies. Of notice, the sample size in most trials have been relatively small and in most of the studies, the intervention has been of short duration and initiated in late pregnancy, whereas several observational studies showing an inverse association between 25OHD levels and birth weight have assessed vitamin D status in early/mid pregnancy [168]. Accordingly, the hypothesis raised by findings from observational studies on effects of vitamin D status on birth weight has not been properly tested in RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, available data from RCTs on effects of vitamin D supplementation on birth weight do not clearly support findings from observational studies. Of notice, the sample size in most trials have been relatively small and in most of the studies, the intervention has been of short duration and initiated in late pregnancy, whereas several observational studies showing an inverse association between 25OHD levels and birth weight have assessed vitamin D status in early/mid pregnancy [168]. Accordingly, the hypothesis raised by findings from observational studies on effects of vitamin D status on birth weight has not been properly tested in RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…The use of a single baseline vitamin D measurement which may not reflect longterm vitamin D status could also affect the validity of the interventional studies. 96 Moreover, the ultrasound criteria of diagnosis of PCOS and of the definition of ovulatory cycles varies among studies this also conducing to the low quality of many of them.…”
Section: 95mentioning
confidence: 99%
“…A high prevalence (60-80%) of vitamin D deficiency among Iranian pregnant women has been reported by several studies (3). Although some studies have reported that vitamin D supplementation during pregnancy may reduce the risk of maternal comorbidities attributed to vitamin D deficiency or insufficiency and help to improve neonatal outcomes (24)(25)(26), there is no general agreement on the optimal dose of vitamin D supplementation in pregnant women (27,28). This lack of inconsistency could be attributed to the differences in study design, dose, type, and timing of vitamin D supplementation, and/or the subjects involved in the study with heterogeneous vitamin D status, and/or methodological differences.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that vitamin D supplementation during pregnancy might reduce the risk of maternal comorbidities attributed to vitamin D deficiency or insufficiency and may help improve neonatal outcomes (24)(25)(26). However, there are still inconsistencies in the results of trials and considerable controversy surrounding the definition of the cut-off values for vitamin D deficiency and insufficiency during pregnancy (27,28). As a result, previous interventional studies failed to determine an appropriate (safe and effective)doseof vitamin D supplementation for pregnant women.…”
Section: Introductionmentioning
confidence: 99%